The differentiation of parental satisfaction with the spatial features of public primary schools: The case of Pendik, Istanbul - Yılmaz, Cengiz; Pakoz, Muhammed Ziya (Konya Technical University, 2021)
Purpose The present study aims to examine the change of parents' satisfaction with the spatial features of public primary schools according to personal, residential, school, and neighbourhood characteristics and to measure to what extent the spatial features explain the overall satisfaction with primary schools. Design/Methodology/Approach Firstly, the study area was divided into 4 clusters by hierarchical clustering method. In proportion to the number of students in each cluster, an online survey was conducted with 807 parents in 19 public primary schools in Pendik between 5-27 May 2020. Personal and residential characteristics obtained from the survey results and school and neighbourhood characteristics obtained from secondary sources were cross-tabulated with the levels of satisfaction on 19 spatial characteristics of the schools. Later, these 19 spatial features were reduced to two basic dimensions with the principal component analysis, and the level of explanation of these dimensions on the overall school satisfaction was revealed by multiple regression analysis. Findings The level of satisfaction of parents with the spatial characteristics of primary schools differs significantly according to personal (15 out of 19), residential (5 out of 19), school (14 out of 19), and neighbourhood (10 out of 19) characteristics. In addition, the parents' satisfaction regarding the spatial adequacies of the primary school has a determinant effect on the overall satisfaction of the parents with the primary school. The most effective factors in the overall satisfaction of parents from primary school are "size of sports fields" and "size of activity spaces". Research Limitations/Implications Similar studies in different cases (both in rural and urban areas), different time periods, and for different education levels should be repeated to compare the results. Social/Practical Implications This research indicates that spatial characteristics should be taken into account in determining the priority improvements starting from the sports fields and activity spaces of schools. Originality/Value The present study evaluates the spatial adequacies of public primary schools and associates it with urbanization and urban planning. It is expected to contribute to the studies to increase the quality of spatial dimensions of primary schools, and consequently urban life quality.
Keywords: Primary Schools; Parental Satisfaction; Spatial Adequacy; Urban Life Quality; Istanbul